Prestress Loss of CFL in a Prestressing Process for Strengthening RC Beams - Xinyan Guo; Dong Liu; Peiyan Huang; Xiaohong Zheng (International Journal of Polymer Science)
A prestressing system was designed to strengthen reinforced concrete (RC) beams with prestressed carbon fiber laminate (CFL). During different prestressing processes, prestress loss was measured using strain gauges attached on the surface of CFL along the length direction. The prestress loss was 50–68% of the whole prestress loss, which is typically associated with CFL slipping between the grip anchors. Approximately 20–27% of the prestress loss was caused by the elastic shortening of the RC beam. An analytical model using linear-elastic theory was constructed to calculate the prestress loss caused by CFL slipping between the anchors and the elastic shortening of the strengthened beams. The compared results showed that the analytical model of prestress loss can describe the experimental data well. Methods of reducing the prestress loss were also suggested. Compared to other experiments, the prestressing system proposed by this research group was effective because the maximum percentage of prestress loss was 14.9% and the average prestress loss was 12.5%.